Geopolymer concrete sulphate resistance - Sahouryeh, D.; Lloyd, Natalie (2013)
Geopolymer concrete is a concrete consisting of non-cement based binder, in the case of this research, the binder was fly-ash activated with sodium silicate and sodium hydroxide. Geopolymer concretes may offer sustainability advantages due to their use of by-products and replacement of cement. Research is required on their structural, mechanical and chemical properties. This research analyzed the effect of different curing regimes and exposure regimes on the sulphate resistance of geopolymer concrete. Geopolymer concrete cylinders that had been steam cured at different temperatures were exposed to a 10% concentrated sodium sulphate solution for one or two months in either fully submerged or partially submerged conditions. Control specimens were not exposed. Precipitate formation occurred on the partially submerged specimens. It was observed that only mass gains occurred in the exposed specimens. XRD indicated no expansive by-products had formed from the exposure and compressive strengths remained unchanged throughout the exposure period. Curing temperature affected the initial rate of strength gain but did not have an impact on the sulphate resistance of the geopolymer concrete.